Clinical and epidemiological characteristics of 25 cases of COVID-19 treated at the Delgado Clinic in Lima - Guzmán-Del Giudice, Oscar Enrique (2020)
Objective: To present the clinical and epidemiological characteristics of patients with COVID-19 treated in a private hospital in Lima. Material and Methods: A descriptive, retrospective and cross-sectional study is  shown. There were 25 cases attended from March 9 to March 27 this year, during the current pandemic, which were treated at the Emergency Service of the Clinic Delgado, Miraflores, Lima. All of them were positive for rRT-PCR testing for coronavirus, performed at the Instituto Nacional de Salud, Lima. Results: Imported cases, 24% or their first contacts, 48%. Twelve (48%) were male. The median age was 38 year-old (range: 11-67 year-old) for males and 44 year-old (range: 33-71 year-old) for women; and, a global median of 40 year-old (range: 11- 71 year-old). Clinical manifestations were: fever 84%, dry cough 84%, dyspnea 56%, odynophagia 56%, coryza 32%, headache 24%, chest pain 24%, diarrhea 16%, myalgia 8%, and fatigue 4%. Comorbidities were found in 16% (high blood pressure, diabetes mellitus type 2, cancer, asthma and hypothyroidism). Forty per cent of cases required hospitalization, and only 8% needed to be admitted to the Intensive Care Unit (ICU). There was no deceased patient. Conclusions: We found that imported and related cases were majority, there were no differences in sex, more frequency between the fourth and fifth decade of life, characteristic clinical picture was present (fever, cough and dyspnea), comorbidities were found, less than a half required hospitalization, characteristic findings in pulmonary TEM were found and very few required entry into the ICU.